Karakteristik Trypsin Inhibitor dan Penjajagan Sebagai Komponen Makanan Fungsional Penderita Diabetes (IIDM) - Bayu Kanetro; Zuheid Noor; Sutardi Sutardi; Retno Indrati (agriTECH, 2005)
Trypsin inhibitors (TI) are substances which, when added to a mixture of a trypsin and a subtrate, bind to the enzyme and render it to decrease in the rate of substrate cleavage. These inhibitors are nonglycosylated, water-soluble (albumin) that account for about 0,2-2 % of the total soluble protein of the legume seeds. Two major families of trypsin inhibitors have been described in legumes: the Bowmen-Brix-type (BBI) and the Kunitz-type inhibitors (KTI). They are distinct families of proteins, as evidenced by their molecular weights, compositions, and amino acid sequences. Because of their unique pharmacological properties, these inhibitors hold considerable promise in clinical applications in their field of medicine. At least one inhibitor in soybeans, the BM, has been shown to have clear anticarcinogenic activity in both in vitro and in vivo carcinogenic Trypsin inhbitors (TI) are substances which, when added to a mixture of a trypsin and a substrate, bind to the enzyme and render it to decrease in the rate of substrate cleavage. These inhibitors are nonglycosylated, water-soluble (albumin) that account for about 0,2 –2 % of the total soluble protein of the legume seeds. Two major families of trypsin inhibitors have been described in legumes: the Bowmen-Birk-type (BBI) and the Kunitz-type inhibitors (K7'I). They are distinct families of proteins, as evidenced by their molecular weights, compositions, and amino acid sequences. Because of their unique pharmacological assay systems. increasing need and awareness for functional food has motivated food scientists and industries to search functional food components and ingredients for certain target group, including functional food for diabetes. Soy TI may enhance the production of more trypsin and probably insulin as well. The dietary 77evokes pancreatic enzyme secretion by forming inactive trypsinT1 complex. As the level of trypsin goes below a threshold level, the pancreas is induced to produce more enzymes. The mediating agent between the enzymes and the pancreas is cholecystokinin (CCK), which is released from the jejunul endocrine cells when the level of trypsin in the intestine becomes depleted. CCK is intestinal hormone which stimulate insulin secretion. Ti regenerated 13-cells which indicate the beneficial effect of TI on the insulin production of the pancreas. These novel findings provide evidence to support the potential utility of TI in the treatment of type 2 diabetes (11DM/ Insulin-Independent Diabetic Mellitus). However, TI are also known as anti nutrient substances and to cause pancreatic hypertrophy.